Speaking for the Social A Catalog of Methods - Knox, Hannah; John, Gemma (punctum books, 2022)
What does it mean to "speak for the social" in projects of technical and infrastructural change? This is the problem that the contributors to Speaking for the Social: A Catalogue of Methods set out to explore through a series of creative interventions that reimagine the role for qualitative social science in understanding and shaping design and engineering projects. The book departs from familiar methods like interviews, surveys, and participant observations, to propose walks, exhibitions, performances, dialogues, online museums, meetings, and staged performances as an array of alternative ways of thinking about and eliciting the social implications of infrastructure projects. Prompted both by a turn to infrastructure and material relations in social research and the concern with social impact and social value in technical projects, this book seeks to outline new ways for social scientists to engage with, critique, and participate in infrastructure design. The chapters build on theoretical attention to the social life of objects like roads, buildings, cities, and environments to devise practical methods that can help make social issues newly visible in infrastructure projects. Individually the entries offer a range of practical methods for "speaking for the social" in technical infrastructure projects. Taken together the book lays the ground for new kinds of collaborative, applied social research embedded in the latest discussions in social theory to explore how social value, impact, and responsibility might be rethought and achieved in the process of designing and engineering social change.